Study on design of crop residue choppers for hard stalks - SONG Hui-zhi; SHENG Kui-chuan; Qian Xiang-qun (浙江大学学报. 农业与生命科学版, 2003)
The main purpose of this project is to investigate the main structure and main design parameters of crop chopper for chopping hard stalks, such as cotton stalk, mulberry branch and so on. A feeding mechanism which could adjust feeding height by itself and the straight knife chopper were designed. Results of the performance test show that the machine this it has to be good to chopping performance, high output have, low grade of energy consumption.